Organic matter, microplastics and macrofaunal communities associated with Posidonia oceanica meadows - Marco Martinez; Roberta Minetti; Emanuela Claudia La Marca; Valeria Montalto; Alessandro Rinaldi; Elisa Costa; Francesca Garaventa; Simone Mirto; Francesca Ape (Marine Environmental Research, 2026)

Surviving in a Warmer Marine World: A Study on the Impact of Thermal Effluent on Posidonia oceanica Meadows and Associated Fish Assemblages in the Maltese Islands - Alessio Marrone; Alessandro Rinaldi; Valeria Montalto; Adam Gauci; Francesca Ape; Henri Ringeard; Marco Spoto; Marco Martinez; Emanuela Claudia La Marca; Simone Mirto; Alan Deidun (Journal of Marine Science and Engineering, 2025)
Ocean warming poses significant threats to coastal ecosystems. This study investigates the impact of thermal effluents from power plants, as proxies for climate-driven temperatures increase, on Posidonia oceanica meadows and associated fish communities. Using a gradient-based approach, we analyzed environmental variables, seagrass indicators, fish assemblages, and functional group (FG) dynamics across a thermal gradient extending from the effluent outfall itself. Results indicate that temperature is the dominant factor influencing P. oceanica, with reduced leaf length, shoot density, and rhizome weight characterizing samples closest to the effluent. Despite compensatory mechanisms, the overall photosynthetic biomass and resilience declined under thermal stress. Fish assemblages exhibited reduced species richness and biodiversity close to the thermal effluent, with opportunistic and thermophilic species dominating. An FG analysis revealed disrupted seasonal patterns, shifts in trophic dynamics, and functional compensation among species, highlighting potential ecological imbalances. Notably, transient predators thrived near the effluent, while more sedentary and temperate species were displaced. These findings underscore the cascading effects of rising temperatures on coastal habitats such as P. oceanica meadows and their associated communities, emphasizing the urgency for conservation measures. By identifying critical thresholds and adaptive responses, this study contributes valuable insights into the consequences of localized impacts of thermal stress on coastal biodiversity and ecosystem services.

The power of Posidonia oceanica meadows to retain microplastics and the consequences on associated macrofaunal benthic communities - Marco Martinez; Roberta Minetti; Emanuela Claudia La Marca; Valeria Montalto; Alessandro Rinaldi; Elisa Costa; Fabio Badalamenti; Francesca Garaventa; Simone Mirto; Francesca Ape (Environmental Pollution, 2024)

Canopy-forming algae improve the colonization success of the vermetid reef-builder Dendropoma cristatum (Biondi 1859) on artificial substrates - Emanuela Claudia La Marca; Francesca Ape; Alessandro Rinaldi; Marco Spoto; Marco Martinez; Enrico Dini; Simone Mirto; Valeria Montalto (Frontiers in Marine Science, 2024)
Positive interactions among foundation species play a crucial role in achieving and maintaining a good state of the marine environment, enhancing the habitat stability, productivity, and the whole ecosystem functioning. In this regard, macroalgal canopies may affect the biotic and abiotic environmental features, improving the habitat quality for the establishment of other sedentary organisms. In this study, we investigated the effect of intertidal canopy-forming algae on the colonization success of the central-Mediterranean vermetid reef-builder Dendropoma cristatum (Biondi 1859) on artificial substrates produced for reef restoration purposes. An in situ experiment was carried out along the northwestern coast of Sicily during the breeding season of the vermetid snails, by using geopolymer concrete settlement discs with a topographic design to facilitate the vermetid settlement. The discs were placed on the seaward reef rim, underneath the macroalgal canopy, and on adjacent control bare reef areas. The canopy effect on the understory algal colonization and the environmental temperature at the vermetid settlement substrate were also surveyed. After 35 days of field exposure, the vermetid settlement increased by 1.7-fold on the discs underneath the macroalgal canopy compared with that on the bare settlement discs. Moreover, the understory algae showed a higher homogeneity and a lower percent cover on the settlement discs underneath the macroalgal canopy. The peaks of temperature were higher on the bare reef, and the macroalgal canopy also reduced temperature variability under maximum sun irradiance during the diurnal low tides. The vermetid settlement was positively correlated to the canopy cover, which, directly or indirectly, improved the success of colonization of the reef-builder snails on artificial substrates. The deployment of settlement discs where canopy-forming algae are naturally present may facilitate the gardening of vermetid clusters that may be translocated to restock the reef-builder density at degraded areas.

The ontogeny-specific thermal sensitivity of the seagrass Posidonia oceanica - Alessandro Rinaldi; Marco Martinez; Fabio Badalamenti; Giovanni D’Anna; Simone Mirto; Lazaro Marín-Guirao; Gabriele Procaccini; Valeria Montalto (Frontiers in Marine Science, 2023)
Introduction The rapid increase in sea-water temperatures and frequency of extreme thermal events have amplified the risk of functional extinction of Mediterranean species such as the endemic long-lived seagrass Posidonia oceanica . Because of the valuable ecological functions and ecosystem services the species provides, understanding the life-stage specific thermal vulnerability is crucial to accurately predict the consequences of current and future global climate change and to protect and conserve existing meadows. Methods To this end, here we report a study on the ontogeny-specific thermal sensitivity of important physiological functions (i.e. respiration and net production) of three different early life history stages of P. oceanica , namely seed, seedling (4-month-old individuals) and 16-month-old plantlet by measuring thermal performance curves (eleven temperatures treatments between 15-36°C with n=8). Results All three stages examined showed photosynthetic activity during light exposure with similar optimal temperatures for both net and gross production. Gross photosynthesis increased with rising temperature up to 28-30°C, subsequently declining at higher temperatures until complete inhibition at 36°C. The metabolic response of seeds was found to be temperature-dependent up to 26°C, while respiration of seedlings and plantlets was almost stable up to 28-30°C, but increased markedly at higher temperatures, resulting in a negative whole-plant C balance at temperatures above 32°C. Overall, our results show that seedlings and plantlets tolerate a wider temperature range (15 - 32°C) than seeds, which experience metabolic and physiological dysfunction from 26-28°C onwards. Discussion These findings suggest that the impact of warming on recruitment in P. oceanica meadows may vary depending on the timing of marine heatwaves (i.e. mid-spring to mid-autumn) and provide useful knowledge to inform restoration programs using early life stages of the species. In conclusion, the study of physiological responses during the early life stages of species is key to identify life history stages that are particularly vulnerable to climate change, which is vital knowledge for ecosystem management and conservation.

Site fidelity of Hippocampus guttulatus Cuvier, 1829 at Mar Piccolo of Taranto (Southern Italy; Ionian Sea) - Cataldo Pierri; Tamara Lazic; Giuseppe Corriero; Frine Cardone; Senem Onen Tarantini; Andrea Desiderato; Simone Mirto; Michele Gristina (Environmental Biology of Fishes, 2020)
Lack of detailed knowledge on ecological niche, life cycles, spatial distribution, reproductive biology and space use strongly affects the selection of useful tools and measures in the conservation of threatened marine species. Especially for sedentary and slow species, behaviour and movement capacities are supposed to be the most important functional traits. Indeed, behavioural variability concerning available space and the close presence of individuals is considered a crucial trait for the population dynamics assessments, especially when disturbances of various causes are present in the environment. The present study aimed to investigate the site fidelity and degree of movement of Hippocampus guttulatus , an emblematic and threatened Mediterranean seahorse species. With this aim, a number of seahorses were tagged and monitored throughout two years within a limited area of the lagoon of Mar Piccolo of Taranto (Southern Italy). The studied individuals were initially morphometrically measured for size, sex and life-cycle stage and subsequently monitored through repeated four-month surveys each year. Obtained results indicated high site fidelity regardless of habitat type. Movement pattern was in line with the data on congeneric species, although values were slightly higher. The analyses showed differences in movement degree among different sexes and life-cycle stages and indicated greater mobility of adult females compared to males and juveniles. The investigated parameters showed a great variability suggesting that even small-scale environmental factors can influence the species mobility. Finally, a change in the population structure has been observed, with the loss of large individuals in 2016 and reduced recruitment in 2017. These findings indicated the possible presence of stressors that could lead to the alteration of the seahorse population at Mar Piccolo of Taranto.

Moving Toward a Strategy for Addressing Climate Displacement of Marine Resources: A Proof-of-Concept - M. Cristina Mangano; Nova Mieszkowska; Brian Helmuth; Tiago Domingos; Tania Sousa; Giuseppe Baiamonte; Giuseppe Bazan; Angela Cuttitta; Fabio Fiorentino; Antonio Giacoletti; Magnus Johnson; Giuseppe D. Lucido; et al. (Frontiers in Marine Science, 2020)

Temporal Changes in Microbial Communities Beneath Fish Farm Sediments Are Related to Organic Enrichment and Fish Biomass Over a Production Cycle - Grazia Marina Quero; Francesca Ape; Elena Manini; Simone Mirto; Gian Marco Luna (Frontiers in Marine Science, 2020)

Predicting shifting sustainability trade‐offs in marine finfish aquaculture under climate change - Gianluca Sarà; Tarik C. Gouhier; Daniele Brigolin; Erika M. D. Porporato; Maria Cristina Mangano; Simone Mirto; Antonio Mazzola; Roberto Pastres (Global Change Biology, 2018)
Defining sustainability goals is a crucial but difficult task because it often involves the quantification of multiple interrelated and sometimes conflicting components. This complexity may be exacerbated by climate change, which will increase environmental vulnerability in aquaculture and potentially compromise the ability to meet the needs of a growing human population. Here, we developed an approach to inform sustainable aquaculture by quantifying spatio‐temporal shifts in critical trade‐offs between environmental costs and benefits using the time to reach the commercial size as a possible proxy of economic implications of aquaculture under climate change. Our results indicate that optimizing aquaculture practices by minimizing impact (this study considers as impact a benthic carbon deposition ≥ 1 g C m −2 day −1 ) will become increasingly difficult under climate change. Moreover, an increasing temperature will produce a poleward shift in sustainability trade‐offs. These findings suggest that future sustainable management strategies and plans will need to account for the effects of climate change across scales. Overall, our results highlight the importance of integrating environmental factors in order to sustainably manage critical natural resources under shifting climatic conditions.

Influence of environmental factors and biogenic habitats on intertidal meiofauna - Francesca Ape; Gianluca Sarà; Laura Airoldi; Francesco Paolo Mancuso; Simone Mirto (Hydrobiologia, 2018)